Macrolide resistance in Mannheimia haemolytica isolates associated with bovine respiratory disease from the German national resistance monitoring program GERM-Vet 2009 to 2020 - Kostova, Valeria; Hanke, Dennis; Kaspar, Heike; Fiedler, Stefan; Schwarz, Stefan; Krüger-Haker, Henrike (Frontiers in Microbiology, 2024)
Data collected from the German national resistance monitoring program GERM-Vet showed slowly increasing prevalence of macrolide resistance among bovine respiratory disease (BRD)-associated Pasteurellacae from cattle over the last decade. The focus of this study was to analyze the genetic basis of antimicrobial resistance (AMR) and the prevalence of multidrug-resistance (MDR)-mediating integrative and conjugative elements (ICEs) in 13 German BRD-associated Mannheimia haemolytica isolates collected between 2009 and 2020 via whole-genome sequencing. Antimicrobial susceptibility testing (AST) was performed via broth microdilution according to the recommendations of the Clinical and Laboratory Standards Institute for the macrolides erythromycin, tilmicosin, tulathromycin, gamithromycin, tildipirosin and tylosin as well as 25 other antimicrobial agents. All isolates either had elevated MICs or were resistant to at least one of the macrolides tested. Analysis of whole-genome sequences obtained by hybrid assembly of Illumina MiSeq and Oxford Nanopore MinION reads revealed the presence of seven novel Tn7406-like ICEs, designated Tn7694, and Tn7724 - Tn7729. These ICEs harbored the antimicrobial resistance genes erm(T), mef(C), mph(G), floR, catA3, aad(3‘‘)(9), aph(3')-Ia, aac(3)-IIa, strA, strB, tet(Y), and sul2 in different combinations. In addition, mutational changes conferring resistance to macrolides, nalidixic acid or streptomycin, respectively, were detected among the M. haemolytica isolates. In addition, four isolates carried a 4,613-bp plasmid with the β-lactamase gene blaROB-1. The detection of the macrolide resistance genes erm(T), mef(C), and mph(G) together with other resistance genes on MDR-mediating ICEs in bovine M. haemolytica may explain the occurrence of therapeutic failure when treating BRD with regularly used antimicrobial agents, such as phenicols, penicillins, tetracyclines, or macrolides. Finally, pathogen identification and subsequent AST is essential to ensure the efficacy of the antimicrobial agents applied to control BRD in cattle.